2011
DOI: 10.1063/1.3549198
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic contact properties of magnetron sputtered Ti3SiC2 on n- and p-type 4H-silicon carbide

Abstract: Epitaxial Ti3SiC2 (0001) thin film contacts were grown on doped 4H-SiC (0001) using magnetron sputtering in an ultra high vacuum system. The specific contact resistance was investigated using linear transmission line measurements. Rapid thermal annealing at 950 °C for 1 min of as-deposited films yielded ohmic contacts to n-type SiC with contact resistances in the order of 10−4 Ω cm2. Transmission electron microscopy shows that the interface between Ti3SiC2 and n-type SiC is atomically sharp with evidence of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…Since 2002 [97] MAX phases have been increasingly synthesized as thin film materials for potential applications such as oxidation-resistant and protective coatings on, e.g., turbine blades [99], bond coatings on sapphire fibers [100], and low friction and oxidation-resistant contacts [101]. In the latter examples the focus is primarily on achieving single-phase films of high density, where steps towards making high quality single crystal samples have mostly been taken since 2010.…”
Section: Thin Film Synthesismentioning
confidence: 99%
“…Since 2002 [97] MAX phases have been increasingly synthesized as thin film materials for potential applications such as oxidation-resistant and protective coatings on, e.g., turbine blades [99], bond coatings on sapphire fibers [100], and low friction and oxidation-resistant contacts [101]. In the latter examples the focus is primarily on achieving single-phase films of high density, where steps towards making high quality single crystal samples have mostly been taken since 2010.…”
Section: Thin Film Synthesismentioning
confidence: 99%
“…for Ti 3 SiC 2 contacts to SiC. [20][21][22] As thin films, the close relatives of Cr 2 GeC, Ti 2 GeC, [23][24][25][26] V 2 GeC, 27,28 and Cr 2 AlC [29][30][31][32][33][34] have all been investigated. From a potential technological viewpoint, the latter two are particularly interesting since they can be grown at a relatively low substrate temperature (450 • C), 27,29 which is essential for deposition onto technologically relevant substrates, such as steels.…”
Section: Introductionmentioning
confidence: 99%
“…19 However, 15 growth of this phase on 4H-SiC was reported to still require high temperature rapid thermal annealing 16 to exhibit Ohmic properties. 20 Transmission electron microscopy studies before and after the annealing 17 process of Ti 3 SiC 2 films showed that annealing resulted in a more ordered interface between the film 18 and 4H-SiC. 20 19 Eliminating the annealing process-step, i.e., synthesizing as-deposited Ohmic contacts through a single-20 step process would be beneficial for the Ohmic contacts to SiC-based devices.…”
mentioning
confidence: 99%
“…20 Transmission electron microscopy studies before and after the annealing 17 process of Ti 3 SiC 2 films showed that annealing resulted in a more ordered interface between the film 18 and 4H-SiC. 20 19 Eliminating the annealing process-step, i.e., synthesizing as-deposited Ohmic contacts through a single-20 step process would be beneficial for the Ohmic contacts to SiC-based devices. 21 In addition, this 21 approach puts forward the possibility to directly synthesize oxygen-barrier capping layers after the 22 main contact deposition without exposing the devices to air for a process-step like annealing, avoiding 23 any risk of oxidation or contamination or any need for a cleaning-step.…”
mentioning
confidence: 99%